2023
DOI: 10.1088/1361-6595/ace280
|View full text |Cite
|
Sign up to set email alerts
|

Thermal dynamics of leader decay and reactivation in long air gap discharges

Abstract: In this study, we present a comprehensive investigation of positive leader discharges, with the aim of enhancing our understanding of leader decay and reactivation. Our approach involved a detailed experimental and computational analysis of the phenomena. Specifically, we employed a time-resolved quantitative Schlieren platform, which provided us with a high spatial resolution (60.0 μm/pixel) and short exposure times (0.37 μs/frame), allowing us to capture the 2D spatial-temporal evolution of gas temperature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In the second zero-off stage shown in figure 8, no electron density drop was detected, which means that t x may be lower than t 2 . Other studies have observed that the initial ionization channel in the air gap can be formed within a few microseconds, well before t 2 [35,36]. • Arcing stage: the arc enters the arcing stage, and its electron density gradually decreases after a rapid decline.…”
Section: Electron Number Densitymentioning
confidence: 99%
“…In the second zero-off stage shown in figure 8, no electron density drop was detected, which means that t x may be lower than t 2 . Other studies have observed that the initial ionization channel in the air gap can be formed within a few microseconds, well before t 2 [35,36]. • Arcing stage: the arc enters the arcing stage, and its electron density gradually decreases after a rapid decline.…”
Section: Electron Number Densitymentioning
confidence: 99%
“…Under the current amplitude of 1 A and the temperature of heavy particles at about 2000 K, the air gap can maintain enough electron number density to generate discharge. As an example, the electron number density of leader discharge with the current in the same low level is in the order of 10 20 ∼ 10 21 m −3 [38]. By analyzing the thermal radius expansion rate of the leader channel, it is shown that the main channel has not yet reached the LTE state [39].…”
Section: Thermodynamic Equilibrium State In the Arcing Stagementioning
confidence: 99%